A combined AHP and ISM-based model to assess the agility of supply chain – a case study. (17th December 2012) - Saleeshya, P.G.; Thampi, Karthik Suresh; Raghuram, P.
An agile supply chain corresponds to the quick responsiveness of an organisation to ever changing market demands without compromising on cost and quality of the product. The textile industry is one such industry having a volatile market demand. This paper is an outcome of a case study conducted in a leading spinning industry in South India. Various enablers and determinants of agility were identified through literature review, field study and industry study. Based on the findings of these studies a multi-level model was developed and the suitability of this model to improve the agility of supply chain was tested. For this, two methodologies – analytical hierarchy process (AHP) and interpretive structural modelling (ISM) were identified as suitable tools. The analysis of the results of AHP and ISM methodologies provide the industry an insight on how the supply chain can be made more agile. Further, the model provides the top management a clear vision of the practices to be implemented and the improvement methods to be adopted by the company for an effective management of supply chains in spinning industries.